A new kind of nanocomposite Xuan paper comprising ultralong hydroxyapatite nanowires and cellulose fibers with a unique ink wetting performance. Issue 69 (9th December 2019) - Shao, Yue-Ting; Zhu, Ying-Jie; Dong, Li-Ying; Zhang, Qiang-Qiang
Abstract : A new kind of Xuan paper comprising hydroxyapatite nanowires and plant fibers with a unique ink wetting performance is reported. Abstract : In the history of civilization, Xuan paper with its superior texture, durability and suitable characteristics for writing and painting, has played an important role in the dissemination of culture and art. Xuan paper has won the reputation of "the king of paper that lasts for 1000 years" and was inscribed on the Representative List of the Intangible Cultural Heritage of Humanity by the Educational, Scientific and Cultural Organization of the United Nations in 2009. However, the surface of the commercial unprocessed Xuan paper has a large number of large-sized pores with a poor resistance to water, allowing ink droplets to easily spread during the writing and painting process. In this study, we report a new kind of nanocomposite Xuan (HNXP) paper comprising ultralong hydroxyapatite (HAP) nanowires and plant cellulose fibers with unique ink wetting performance, high whiteness and excellent durability. The as-prepared HNXP paper sheets with various weight ratios of ultralong HAP nanowires ranging from 10% to 100% are all superhydrophilic with a water contact angle of zero. In contrast, the ink contact angle of the HNXP paper can be well controlled by adjusting the weight ratio of ultralong HAP nanowires, and the ink contact angle of the HNXP paper increases with increasing weight ratio of ultralong HAP nanowires. The experimental results show the unique ink wetting behavior of the as-prepared HNXP paper, which is absent in the traditional Xuan paper. This new kind of nanocomposite Xuan paper comprising ultralong hydroxyapatite nanowires and plant cellulose fibers is promising for applications in calligraphy and painting arts.